A novel approach to solve the split delivery vehicle routing problem. (12th January 2016) - Chen, Ping; Golden, Bruce; Wang, Xingyin; Wasil, Edward
Abstract: The split delivery vehicle routing problem (SDVRP) is a relaxed version of the classic capacitated vehicle routing problem (CVRP). Customer demands are allowed to split among vehicles. This problem is computationally challenging and the state‐of‐the‐art heuristics are often complicated to describe and difficult to implement, and usually have long computing times. All these hinder their application by practitioners to solve real‐world problems. We propose a novel, efficient, and easily implemented approach to solve the SDVRP using an a priori split strategy, that is, each customer demand is split into small pieces in advance. Our computational experiments on 82 benchmark instances show that our algorithm is overall much more efficient and produces results that are comparable to those from the state‐of‐the‐art approaches.